2011
DOI: 10.1111/j.1556-4029.2011.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Determination of Sex: Metric and Nonmetric Traits of the Adult Pelvis from 3D Computed Tomography Models*,†

Abstract: Examination of the adult os coxae and sacrum is one of the most common methods of sex estimation from bone. Medical imaging, such as computed tomography (CT), provides the opportunity for three-dimensional (3D) imaging of the skeleton from clinical scans of known individuals in situ. In this study, a randomly selected subset of abdominopelvic CT-derived models were used to evaluate simple, repeatable metric methods of sex estimation based on a combination of obstetric measurements and the traditionally nonmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
99
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 28 publications
11
99
1
Order By: Relevance
“…This result agrees with those of Decker et al, 2011, whose study was conducted on pelvi-abdominal CT-derived models of patients at the University of South Florida College of Medicine, using the same 20 variables [8]. It also agrees with Djorojevic et al, 2014, who concluded the presence of greatest differences between both sexes in innominate height (IHM) as it reflects the overall size of the body and it is it is generally higher in men [4].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This result agrees with those of Decker et al, 2011, whose study was conducted on pelvi-abdominal CT-derived models of patients at the University of South Florida College of Medicine, using the same 20 variables [8]. It also agrees with Djorojevic et al, 2014, who concluded the presence of greatest differences between both sexes in innominate height (IHM) as it reflects the overall size of the body and it is it is generally higher in men [4].…”
Section: Resultssupporting
confidence: 82%
“…It shows 100% overall accuracy, with 100% sensitivity for male identification and 100% specificity for female identification. This result is typically in agreement with those of Decker et al, 2011 [8].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For the current study, the authors chose to validate a retrospective data source. The slice thickness in the current research was smaller or comparable (0.625 mm and 1.25 mm) to the majority of recent publications (0.75 mm to 1.25 mm) that investigated the accuracy of measurements collected on CT images [2,3,48]. However, a smaller slice thickness should be considered if designing a prospective study.…”
Section: Discussionmentioning
confidence: 77%
“…To date, however, few authors have applied CT scan in the field of anthropometry to achieve accurate standards measurements in vivo using femur [10].…”
Section: Introductionmentioning
confidence: 99%